2013
DOI: 10.1016/j.compedu.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Addressing drop-out and sustained effort issues with large practical groups using an automated delivery and assessment system

Abstract: Abstract:The acquisition of programming skills specially in introductory programming courses poses an important challenge for freshmen students of engineering programs. These courses require students to devote a sustained effort during the whole course and a failure to do so may contribute to not passing the course. However, it is difficult for the teaching staff to deploy measures to enforce a pattern of continuous work without significantly increasing the required management tasks. A significant reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
10
0
2
Order By: Relevance
“…Notably, students who achieve high score in homework assessments perform significantly better in the final exam than those who do not (Veerasamy;D'Souza;Lindén;Kaila;Laakso;& Salakoski, 2016). In addition, homework is an important determinant of student final exam marks (Veerasamy;D'Souza;Lindén;Kaila;Laakso;& Salakoski, 2016; de-la-Fuente-Valentín, Pardo, & Kloos, 2013). Similarly, a review of literature review related to homework in programming courses indicates that homework has a positive effect on student learning outcomes and can be considered as the significant predictor of learning achievement (Su, Huang, Yang, Ding, & Hsieh, 2015).…”
Section: Formative Assessment Tasks As Predictors Of Student Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, students who achieve high score in homework assessments perform significantly better in the final exam than those who do not (Veerasamy;D'Souza;Lindén;Kaila;Laakso;& Salakoski, 2016). In addition, homework is an important determinant of student final exam marks (Veerasamy;D'Souza;Lindén;Kaila;Laakso;& Salakoski, 2016; de-la-Fuente-Valentín, Pardo, & Kloos, 2013). Similarly, a review of literature review related to homework in programming courses indicates that homework has a positive effect on student learning outcomes and can be considered as the significant predictor of learning achievement (Su, Huang, Yang, Ding, & Hsieh, 2015).…”
Section: Formative Assessment Tasks As Predictors Of Student Performancementioning
confidence: 99%
“…Keeping these points in mind, the objective of the research reported in this paper is to develop a predictive model with selected predictor variables using data mining techniques to predict student performance and at-risk students in a programming course (at university level) to make proactive measures in teaching and learning. courses for novices and the difficulty of learning to program also dissuades students from other programs to avoid taking programming and to select alternative courses (de-la-Fuente-Valentín, Pardo, & Kloos, 2013;Ali & Smith, 2014). Many teaching techniques and educational technologies have been developed by researchers to improve student learning outcomes in programming (Borra & Ciaccio, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exploring the potential of technology for improving teachers' understanding of student misconceptions can be important. In computer science education, one widely used instructional tool is the automated assessment system (De-La-Fuente-Valentín, Pardo, & Delgado Kloos, 2013;Douce, Livingstone, & Orwell, 2005). An automated assessment system is a tool that can automatically evaluate the correctness of students' programs by applying certain assessment techniques and algorithms.…”
Section: Eurasia J Math Sci and Tech Edmentioning
confidence: 99%
“…High failure rates were reported among in introductory programming courses poses an important challenge for freshmen students of many programs. These courses require students to devote a sustained effort during the whole course and a failure to do so may students taking programming courses [20][21][22].…”
Section: Predictors Of Programming Performancementioning
confidence: 99%